Primary School Student Advocacy As a Preventive Measure For Bullying Behavior - Maulana, Oka (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2023)
Social facts show a decline in student behavior, where cases of bullying perpetrated by students at every level of formal education are increasing day by day. The high number of bullying cases not only results in physical injuries but also psychological trauma for the victims. So as a teacher, this becomes a worry, and we try to find a solution of bullying by elementary school students. To break the chain of bullying by elementary school students, the author advocates for students at 010 Kunto Darussalam State Elementary School using a Participatory Action Research Approach. At the locus advocacy, they take preventive by providing examples to follow, emulate, and internalize the values of Religious Education and Citizenship Education subjects in elementary school students. Preventive efforts are also carried out with character education so that they become human beings. Thus, after these values are internalized within students, it will become a habit for them to live their lives and become good individuals.